Consumer Behavior in Their Buying Decision Process of Agro-Geographical Indication Products in Yogyakarta - Hildha Nurmalasari Dewi; Anggoro Cahyo Sukartiko; Agung Putra Pamungkas (APTA and DTIP FTP UGM, 2017)
Geographical Indication (GI) defined as a designation used for products that strongly attached with their origins. The purposes of the study are: to find out consumer behavior at all buying decision stages, to see their perception of agro-geographical indication products, and to determine the most considered attributes in buying decision process of the products. Questionnaires had been distributed to 240 respondents using a purposive sampling technique to collect relevant data for achieving the research’s purposes. Population proportion and Fishbein multi-attributes model were used to analyze the obtained data. Buying decision process of agrogeographical indication products was differentiated into five stages, namely: need recognition; information gathering; alternatives evaluation; purchase decision; and post-purchase behavior. We found the importanceof product’s authenticity at the first stage of buying decision process; the internet and social media as the primary source for GI’s product information at the second stage; and product indigenousness at the third stage. At the fourth stage, most consumers bought the product in the traditional market; and the fifth stage, we found that most of them satisfied with the products, its price, and considered to purchase more in the future. Most of the consumer has a good perception of GI products. However; they had not prioritized GI products over other similar products. The quality of the GI products was the most considered factor in buying decision.